The Text Matrix as a tool to increase the cohesion of extensive texts. - De Sordi, José Osvaldo; Meireles, Manuel; Oliveira, Osvaldo Luiz (Journal of the Association for Information Science & Technology, 2016)
The significant amount of time needed to prepare concise and cohesive texts is among the reasons why extensive texts proliferate in organizations. Extensive documents are more likely to have low cohesion among their various sections, which may lead the reader to perceive the information as being of low quality. This research addresses this issue by presenting a tool ( Text Matrix) composed of procedures and algorithms coded in software, with the aim of analyzing cohesion between the text sections in extensive documents. A design science research approach was applied to develop, test, and prove the usefulness of the Text Matrix. A total of 127 academic advisors and advisees were trained to use the Text Matrix and apply it in the development of the extensive text of dissertations. An analysis both of those users' perceptions and of variations in network density among 41 extensive texts that they improved through the analyses performed by the artifact proposed in the present study demonstrated the ease of operation and effectiveness of the Text Matrix to identify parts of extensive texts associated with cohesion failures that could be connected by cohesion devices or even excluded from the extensive text.